A New Composite Implicit Iteration Process for Generalized Asymptotically quasi-nonexpansive Mappings in Banach Spaces - Sahu, Vinod Kumar (Journal of Global Research in Mathematical Archives(JGRMA), 2017)
The purpose of this paper is to prove the strong convergence of a new modiï¬ed composite implicit iterative process with errors for two ï¬nite families of generalized asymptotically quasi-nonexpansive mappings in framework of Banach space. Our results extend some known results. MSC (2010): 47H09, 47H10, 65J15. Key Words : Generalized asymptotically quasi-nonexpansive mapping, composite implicit iterative scheme, uniformly continuous, Banach space.